Annuities and Other Retirement Products : Designing the Payout Phase - Rocha, Roberto; Vittas, Dimitri; Rudolph, Heinz P. (World Bank, 2012)
This book examines recent changes in the landscape of retirement products and annuity markets in five countries. All the selected countries (Australia, Chile, Denmark, Sweden, and Switzerland) have mandatory or quasi-mandatory savings schemes. But they also exhibit significant differences in the structure of their pension systems, the relative importance of public pillars, the role and structure of private provision, the level of annuitization, and the structure and focus of their regulatory frameworks. Five studies have been commissioned to examine the state of annuity markets in each of these countries. The findings of these studies are summarized in the last five chapters of this book. The chapters of this book is discusses the various risks faced by pensioners and the risk characteristics of alternative retirement products, and it reviews the risks faced by providers of retirement products and the management and regulatory challenges of dealing with those risks. The chapter then discusses the risks faced by providers and reviews the challenges of various regulatory issues, ranging from the institutional organization of the market for retirement products to the regulation of marketing and pricing policies and the regulation of risk management. The chapter concludes with a brief summary of main points and conclusions.